Primary human endothelial cells secrete agents that reduce responsiveness to lysophosphatidic acid (LPA). Issue 4 (28th June 2012) - Park, Eun Young; Kazlauskas, Andrius
Abstract : The plasma level of LPA (lysophosphatidic acid) (200–600 nM) is well within the range that promotes proliferation and migration of vascular ECs (endothelial cells), yet vessels are quiescent and stable. In this report, we considered one explanation for this paradox: that ECs secrete agents that attenuate responsiveness to LPA. Indeed, we observed that CM (conditioned medium) from confluent, quiescent cultures of primary HUVECs (human umbilical vein ECs) contained an agent that inhibited LPA-mediated signalling events and cellular responses. The putative inhibitor, which we tentatively call ILMR (inhibitor of LPA-mediated responsiveness) seemed to act on cells (instead of at the level of LPA) by suppressing the ability of LPA receptor 1 to signal. The amount and/or activity of ILMR was regulated by growth factors; exposing HUVECs to VEGF-A (vascular endothelial growth factor A), but not bFGF (basic fibroblast growth factor), reduced the amount and/or activity of ILMR in CM. We conclude that in addition to promoting angiogenesis directly, VEGF-A can also act indirectly by modulating the bioactivity of angiomodulators such as LPA.